Design thinking: the illustrated book as a strategy for psycho-educational intervention with children under oncological treatment - Demarchi, Ana Paula Perfetto; Suzuki, Fernanda Hiromi; Soares, Maria Rita Zoéga (Seven Editora, 2023)
illions of cancer cases are diagnosed each year, including in children. The success of treatment depends on adherence and one of the strategies for adherence is the use of books or manuals. The present work aims to present Design Thinking and show how this method can contribute to the creation of an imagetic material to support psychoeducation. Bibliographic research and interviews with the author of the book "I’m sick, now what? Guidelines for children with cancer", with a psychologist from the Hospital do Câncer de Londrina, and with mothers of cancer patients. The methodology used was Design Thinking, which facilitated the generation of ideas, project direction and working together with professionals from various areas of knowledge, resulting in a collection of children’s books for children, parents and professionals. DOI: https://doi.org/10.56238/devopinterscie-037